Evaluation of the tactics for small- and medium-sized toy factories in China to deal with European and US toy safety requirements. (7th July 2021) - Kwong, CW; Mak, SL; Li, CH
China is the largest exporter of toys. Small- and medium-sized toy factories usually face various challenges when they deal with quality aspects and toy safety requirements. After a literature review and pilot study, a conceptual framework to improve factories' capabilities in dealing with European and US toy safety requirements through Toy safety assessment, Cost and resources optimization, Industry 4.0, ISO 19600:2014 (which has become ISO 37301:2021), and Web-based product compliance platforms, is proposed. In mid-2020, a questionnaire was designed, and an internet questionnaire survey empirical study was conducted. The statistical results from 107 responses suggested that Toy Safety Assessment, ISO 19600:2014 (ISO 37301), and Industry 4.0 have made positive and significant contributions to factories' capability to respond to European and US toy safety requirements. The study identifies and prioritizes the factors to improve toy factories' capabilities in dealing with European and US requirements.